Real Gross Product in OECD Countries and Associated Purchasing Power Parities - Hill, Peter (OECD Economics Department Working Papers, 1984)
This report contains a new set of results on the levels of real per capita GDP and its main components in OECD countries in 1980, with estimates for later years upto 1984. Real per capita GDP is obtained by valuing the goods and services in different countries at a fixed set of prices, namely, the average prices prevailing at the time within the group of countries covered. This procedure is essentially the same as that used to measure volume changes over time within a single country when the fixed prices of some base year are used to compile expenditure or output series at constant prices. The international measures of real per capita GDP for different countries can therefore be interpreted in the same way as the volume indices which are used to measure real rates of growth within a single country. These international volume measures may be contrasted with measures of per capita GDP which are frequently obtained by converting data for different countries into a single currency ...